Heterogenität SHANK2-bedingter neuropsychiatrischer Störungen: Neurogenetik des Sozialverhaltens - Rappold, Gudrun; Sprengel, Rolf (Biospektrum, 2020)
The significance of SHANK proteins in human behaviour is evidenced by the wide spectrum of neuropsychiatric disorders in patients with SHANK mutations and the variety of behavioural impairments of Shank knockout mouse lines. Differentially expressed SHANK isoforms might explain this complexity. The analysis of three conventional and seven conditional Shank2 mouse lines showed that the type of SHANK2 mutation critically determines the physiological and behavioural impairments.
Gesehen am 11.11.2021